Kepemimpinan Fidel Castro Terhadap Kebebasan Berpolitik di Negara Kuba - Ayunda, Najla Dara; Dewi , Anggrelita Mutiara Salsabila; Pramesyanti, Chifra Zeila; Megantara, Mahesha Suryo; Zusrieka, Marsya (Journal of Politics and Democracy, 2025)
Cuba is a country located in the Caribbean Islands that adheres to a socialist system in its country, this socialist system is believed to have succeeded in providing social security and equal distribution of education for the Cuban people. The 1959 Cuban Revolution led by Fidel Castro successfully adopted a socialist political system based on the principles of Marxism-Leninism, after which on January 1, 1959 marked the revolutionary movement led by Fidel Castro succeeded in overthrowing the dictatorial regime of Fulgencio Batista. The purpose of this study is to analyze the impact of political freedom implemented by Fidel Castro in Cuba. This research uses a secondary research approach by collecting data from relevant sources, such as books, journals, articles, and reliable sources. The results of this study show that Fidel Castro's leadership was instrumental in creating political conditions and political ethos in Cuba, Castro's distinctive rhetoric and ability to mobilize the people made it possible to uphold the ideology of socialism and implement it. However, this leadership was associated with the weakening of the political opposition and the lack of control over the media.